Mapping the Soil Fertility at Arabica Coffee Field in Lumban Julu District, Toba Samosir District - Joko Erikson Sihombing; Posma Marbun; Purba Marpaung (Jurnal Agroekoteknologi, 2019)
Lumban Julu Subdistrict is one of  the producer Arabica coffee in Toba Samosir District. Know the soil fertility status Very important to increase production Arabica coffee. This research aims to mapping the soil fertility in arabica coffee field in Lumban Julu Subdistrict, Toba Samosir district. It was located at Arabica Coffee Field in Lumban Julu Sub-district, Toba Samosir District. Soil samples were taken from each Soil Map Unit (SMU) and it will be analyzed at the Laboratory. Observed parameters are cation exchange capacity (CEC), bases saturation, C-organic, P-total and K-total. The research showed that all soil fertility status of SMU 1 until SMU 8 were low criterion.Keywords: arabica coffee, mapping, soil fertility status